Intermediate hydroxide enforced electrodeposited platinum film for hydrogen evolution reaction - Yadav, Jyotiprakash B.; Park, Jong-Won; Cho, Yong-Jin; Joo, Oh-Shim (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Competitive catalytic activity of platinum (Pt) makes it as a promising cathode material for hydrogen evolution reaction. But cost of Pt makes it impractical for its use in commercial applications. Unlike literature known methods, our study entails on a methodology of ambient temperature electrodeposition of Pt films, without the use of a complexing agent or pH adjustments or both. Pt films are deposited in an electrochemical bath, which is prepared by adding platinum chloride complex [H2PtCl6 center dot x H2O] in triple-distilled water. Pt films deposited at different potentials are analyzed for their morphological (SEM), structural (XRD), electrochemical study (Cyclic Voltammetry and Linear sweep measurements). The growth and catalytic activity of Pt film show strong dependence on applied deposition potential (-0.25 V to -0.40 V) and reduction kinetics of [PtCl6](2-) or [Pt(OH)Cl-5](2-) intermediate hydroxide ions, that occurs during the process. Binding energy (BE) of Pt(4f(7/2)) peak in a film increases to 72.4 eV (until -0.30 V), which slightly decreases at a deposition potential of -0.40 V. XRD data show changes along (111) and (200) planes, to which [PtCl6](2-) and [Pt(OH)Cl-5](2-) intermediate hydroxide ions are found to be responsible. The average particle size with respect to applied potential, obtained from SEM data is found to be 25-40 nm. The catalytic activity (Peak current density in cyclic voltammetry) versus deposition potential data is correlated with Pt film formation by reduction of intermediate hydroxide ions. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: THIN-FILMS; FUEL; DEPOSITION